Environmental Sustainability in Viticulture as a Balanced Scorecard Perspective of the Wine Industry: Evidence for the Portuguese Region of Alentejo - Gomes, Maria José (2021)
The traditional four-perspective Balanced Scorecard (BSC) model is suitable for a wide variety of organizations. Other dimensions of analysis can be carried out and other perspectives can be considered in each BSC, depending on the specific characteristics of each organization or industry. This paper presents evidence that justifies and validates the inclusion of a new perspective: ‘environmental sustainability in viticulture’in a BSC that has been developed for the Wine Industry of the Alentejo Region (Portugal) for 2021–2030. The research was performed according to the exploratory sequential design method, which combines in vivo (interviews and questionnaires) and in vitro (literature review and secondary data) research. The content analysis technique, supported by the NVivo software, was used to treat and analyze the data obtained from the interviews, to discover the explicit meanings of the interviewees’ speeches. A principal component analysis and a set of statistical analyses were performed to support the identification of perspectives to be considered in this industrial BSC. The results suggest that environmental sustainability (in viticulture) should be considered as a new strategic perspective to be included in the BSC, with a focus on future certification of environmentally sustainable production (grapes, wine, and wineries). The new perspective represents the competitive challenge of environmental sustainability and enhancement of endogenous resources for the Alentejo Wine Industry, as well as for other wine regions that share the same challenges and concerns. The results also offer an opportunity for competitive benchmarking for companies, industries and governments that operate in similar situations.